Report on the 5th International Workshop on Networking Meets Databases - Loo, Boon Thau; Saroiu, Stefan (ACM SIGMOD Record and ACM Operating Systems Review (OSR), 2009)
The Workshop on Networking Meets Databases (NetDB) is a venue that aims to bring together researchers from the systems and networking community and the database community. Many current research areas, such as cloud computing, data-center networking, sensor networks, network management, or social networks, raise research problems that lie at the boundary between these two communities. The workshop’s goal is to foster an environment in which researchers from both communities can discuss ideas that will shape and influence these emerging research areas. The workshop encourages submissions of early work, with novel and interesting ideas. The expectation is that work introduced at NetDB, once fully thought through, completed, and described in a finished form, may be relevant to conferences such as SOSP, OSDI, SIGCOMM, SIGMOD, VLDB, NSDI, or ICDE. Traditionally, NetDB has been co-located with either the IEEE International Conference on Data Engineering (ICDE’05, ICDE’06, ICDE’08) or the USENIX Symposium on Networked Systems Design and Implementation (NSDI’08). This year is the first time when the workshop was co-located with the ACM Symposium on Operating Systems Principles (SOSP). By co-locating with SOSP, we aimed at raising the interest from the wider systems community on topics relevant to NetDB.